Molecular Identification of Lactic Acid Bacteria Occurring in Must and Wine - Sebastian, P.; Herr, P.; Fischer, U.; König, H. (South African Journal of Enology and Viticulture, 2011)
A specifically amplified polymorphic DNA-polymerase chain reaction (SAPD-PCR), a molecular fingerprinting method based on the amplification of specific gene sequences, was applied in order to allow a rapid identification of lactic acid bacteria (LAB) occurring in must and wine. The applicability of this method was confirmed with isolated strains from different wine samples from the German wine growing region Palatinate. In addition, the formation of biogenic amines by the isolated strains was studied. More than half of the bacterial isolates from 50 red and white wine samples were able to produce biogenic amines. General health concerns related to biogenic amines in must and wine underline the need for an identification of these species. The majority of the isolated strains were assigned to the species Lactobacillus brevis. The major biogenic amines in the investigated wines which were detected by thin-layer chromatography and HPLC were tyramine, histamine and ethylamine.